Fuel requirements of spark ignition engines - Kalghatgi, G; Stone, R (SAGE Publications, 2017)
This paper reviews the fundamental requirements of liquid hydrocarbon fuels for spark-ignition engines, namely that the fuel should vaporize satisfactorily and burn in a controlled manner. The phenomenon of knock and the development of the octane scale are discussed. The variation in pressure time histories between engines is discussed, along with how this leads to different fuel requirements. The difference in the octane rating tests, and how engine down-sizing exacerbates these differences in the pressure time histories is discussed. The applicability of RON and MON to modern engines is reviewed, along with the phenomenon of low speed preignition and mega-knock. The effect of hydrocarbon fuel distillation characteristics on drivability and emissions is reviewed, and placed in a historical context and the current legislative requirements. Brief mention is made of other fuel requirements such as density, gum content and aromatic content.